Case report: Common clonal origin of concurrent langerhans cell histiocytosis and acute myeloid leukemia - Kazama, Shintaro; Yokoyama, Kazuaki; Ueki, Toshimitsu; Kazumoto, Hiroko; Satomi, Hidetoshi; Sumi, Masahiko; Ito, Ichiro; Yusa, Nozomi; Kasajima, Rika; Shimizu, Eigo; Yamaguchi, Rui; Imoto, Seiya; et al. (Frontiers in Oncology, 2022)
Background: Acute myeloid leukemia (AML) and Langerhans cell histiocytosis (LCH) are distinct myeloid neoplasms, but either originates from a compartment of hematopoietic stem cells or myeloid progenitor cells. However, reports of concurrent LCH and AML is rare. Herein we report a novel case of concurrent AML and LCH which shared same driver mutations, strongly suggesting a common clonal origin. Case Presentation: An 84-year-old female presented with cervical lymphadenopathy and pruritic skin rash on the face and scalp. Laboratory tests revealed pancytopenia and elevated LDH, and systemic lymphadenopathy and splenomegaly by computed tomography. Bone marrow specimens showing massive infiltration of MPO-positive myeloblasts, whereas S-100 and CD1a positive atypical dendritic cell-like cells accounted for 10% of the atypical cells on bone marrow pathology, suggesting a mixture of AML and LCH. Biopsy specimen of a cervical lymph node demonstrated accumulation of atypical cells which were positive for S-100 and CD1a. Next generation sequencing revealed four somatic driver mutations (NRAS-G13D, IDH2-R140Q, and DNMT3A-F640fs / -I715fs), equally shared by both lymph node and bone marrow, suggesting a common clonal origin of concurrent LCH and AML. Prednisolone and vinblastine were initially given with a partial response in LCH, and peripheral blood blasts also disappeared for as long as 3 months. Salvage chemotherapies with low dose cytarabine and aclarubicin were given for relapse and with a partial response in both LCH and AML. She died from pneumonia and septicemia on day 384. Conclusion: Our case demonstrates a common cell of origin for LCH and AML with a common genetic mutation, providing evidence to support the proposal to classify histiocytosis, including LCH, as a myeloid/myeloproliferative malignancy.